2002
DOI: 10.1074/jbc.m202625200
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Nuclear Localization of Mammalian Target of Rapamycin in Normal and Malignant Cells in Culture

Abstract: Mammalian target of rapamycin (mTOR) controls initiation of translation through regulation of ribosomal p70S6 kinase (S6K1) and eukaryotic translation initiation factor-4E (eIF4E) binding protein (4E-BP). mTOR is considered to be located predominantly in cytosolic or membrane fractions and may shuttle between the cytoplasm and nucleus. In most previous studies a single cell line, E1A-immortalized human embryonic kidney cells (HEK293), has been used. Here we show that in human malignant cell lines, human fibrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(112 citation statements)
references
References 32 publications
8
99
1
4
Order By: Relevance
“…S6K1 drives translation of 5 0 TOP (terminal oligopyrimidine tract) mRNAs, and 4E-BP1 inhibits the mRNA cap-binding protein elF4E (Schmelzle and Hall, 2000). 4E-BP1 and S6K1 were detected exclusively in the cytoplasm of cancer cells (Zhang et al, 2002). We suggest that increased cytoplasmic mTORC1 complex may activate signalling to cytoplasmic S6K1 and 4E-BP1 and contribute to tumour progression, although 4E-BP1 and S6K1 were not investigated in this study.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…S6K1 drives translation of 5 0 TOP (terminal oligopyrimidine tract) mRNAs, and 4E-BP1 inhibits the mRNA cap-binding protein elF4E (Schmelzle and Hall, 2000). 4E-BP1 and S6K1 were detected exclusively in the cytoplasm of cancer cells (Zhang et al, 2002). We suggest that increased cytoplasmic mTORC1 complex may activate signalling to cytoplasmic S6K1 and 4E-BP1 and contribute to tumour progression, although 4E-BP1 and S6K1 were not investigated in this study.…”
Section: Discussionmentioning
confidence: 79%
“…This finding suggests that changes in the localisation of p-mTOR may be involved in tumour progression. Other investigators reported that m-TOR is mainly localised in the cytoplasm (Janus et al, 2005;Bachmann et al, 2006), although a small fraction of mTOR is found at a steady state in the nucleus in both normal and malignant cells (Zhang et al, 2002). mTOR is part of two distinct complexes: mTORC1 containing raptor and a mammalian orthologue of yeast Lst8p (mLST8; also known as GbL), and mTORC2 containing rictor, mLST8, and sin1 (also known as mitogen-activated protein-kinase-associated protein 1) (Sarbassov et al, 2005;Petroulakis et al, 2006;Rosner and Hengstschläger, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subcellular localization of TOR is likely signal dependent and cells observed under different conditions yield different results. Although a nuclear localization has been reported for TOR (Zhang et al, 2002), TOR has also been found in the cytoplasm and might shuttle between cytoplasm and nucleus (Sabatini et al, 1999;Kim and Chen, 2000). Drenan et al demonstrate a predominantly perinuclear distribution of TOR and show a close association with ER and the Golgi apparatus (Drenan et al, 2004).…”
Section: Oncogenic Transformations By Rheb Mutants H Jiang and Pk Vogtmentioning
confidence: 99%
“…1); constitutive nuclear localization of mTOR is observed in several tumor cell lines. 22,23 A distinct set of residues in the HEAT repeat region determines mTOR localization to endoplasmic reticulum (ER) and=or Golgi membranes. 24 The ER may provide a physical platform for mTOR metabolic sensing functions, control of the ER stress response, 25 and coordination of mTOR signaling to the translational and transcriptional machinery.…”
Section: The Molecular Organization Of Mtormentioning
confidence: 99%